Wind Speeds Estimation on the Ground Level for Windmills Site Selection - Ali, Saleh; Mahdi, Alaa; Shaban, Auday (Iraqi Journal of Science, 2024)
In the last few years, the world toward attention to the renewable and cleanenergy sources in order to reduce the environmental pollutions and reduce the coast.Therefore, the windmills technology was essential in these applications. In thispaper, the climatic data and geographic information system (GIS) facilities wereused to study and produce the wind speed map on the ground level for Iraq country.Many Field data, (climatic monitoring) from the periods, (1953-1970) and (1971-2010) were collected and prepared. The data source was the Iraqi metrologicaldepartment, this establishment operates and control wide climatic stationsdistributed around country. Many image processing and remote sensing techniqueswere used to present the results. The full Iraq photomap of Landsat TM (bands 1, 3,5) with 28.5m in spatial resolution was used to overlay the results. The output ofresearch was a photomap that locates the best sites for windmills .The locations havebeen selected through certain criteria. The results indicate that the Nasrya, Basrah,Nukhaib, Alhai and Hadeetha are promising places for establishing wind turbine dueto the best wind velocities values